2000
DOI: 10.1080/03091900050204269
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a two-dimensional electrocutaneous cognitive feedback system for use in paraplegic standing

Abstract: Fatigue of electrically activated paralysed muscles is a major factor limiting the duration of functional electrical stimulation (FES) supported paraplegic standing. Fatigue can be significantly delayed by changing the posture. Since paralysed individuals are deprived of proprio- and exteroception from the lower limbs they are not aware of the posture and loading of their paralysed legs. If suitable cognitive feedback (CF) information about posture in the sagittal and frontal planes is provided, they might be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The typical neuroprosthesis user would have uncompromised visual feedback, but in tact sensory feedback would be restricted to portions of the body innervated above the level of injury. Studies investigating cognitive feedback about whole-body leaning using electrocutaneous [Matjacic, Jensen et al 23] and vibrotactile [Kadkade, Benda et al 24] stimulation to just the skin surface have shown improvement in balance performance. Such findings motivate the development of balance prostheses that augment sensory capabilities of the user such as touch and proprioception in relation to the lower extremities and facilitate the integration of that feedback for whole-body FNS standing control.…”
Section: - Overviewmentioning
confidence: 99%
“…The typical neuroprosthesis user would have uncompromised visual feedback, but in tact sensory feedback would be restricted to portions of the body innervated above the level of injury. Studies investigating cognitive feedback about whole-body leaning using electrocutaneous [Matjacic, Jensen et al 23] and vibrotactile [Kadkade, Benda et al 24] stimulation to just the skin surface have shown improvement in balance performance. Such findings motivate the development of balance prostheses that augment sensory capabilities of the user such as touch and proprioception in relation to the lower extremities and facilitate the integration of that feedback for whole-body FNS standing control.…”
Section: - Overviewmentioning
confidence: 99%